Evaluating Representative State Samples of Seventh-Grade Students’ Ability to Critically Evaluate Online Information - Elena Forzani; Cheryl Maykel (62nd Annual Conference of the Literacy Research Association, 1998)
This study investigated the extent to which a sample of seventh grade students (n = 591) in Connecticut critically evaluated online information both within and across three different assessment formats. The formats included Closed (simulated Internet environment requiring constructed responses), Open (actual, unrestricted Internet environment requiring constructed responses), and Multiple Choice. Results indicated that critical evaluation was more difficult for students than the three other online reading and research skill areas assessed (i.e., Locate, Synthesize, and Communicate) in all three formats combined, and was one of the most difficult of the skill areas within each of the three formats. Additionally, among the four critical evaluation tasks assessed (e.g., finding out the author of a website, determining if that author is an expert, evaluating the author’s point of view, and evaluating the overall reliability of a website), evaluating the author’s expertise and evaluating the overall reliability of a website was the most difficult for students. Finally, students performed better on critical evaluation tasks in the Multiple Choice format than they did in either of the two performance-based formats. Findings suggest that critical evaluation persists as one of the most difficult online comprehension and research skills for students, especially when measured in a performancebased format.
Keywords: école secondaire; évaluation; lecture numérique; recherche d'information